PERAN DUKUNGAN ORGANISASI DAN MODAL PSIKOLOGIS TERHADAP PSYCHOLOGICAL OWNERSHIP - Krisanti, Yoana Vina; Rostiana, Rostiana; Lie, Daniel (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2017)
This research is conducted to find the role of perceived organizational support and psychological capital to psychological ownership of the employees of PT ABC. Perceived organizational support as an independent variable has three dimensions which consist of fairness, supervisor support, and organizational reward. Psychological capital as an independent variable has four dimensions which consist of self-efficacy, hope, optimism, and resilience. As a dependent variable, psychological ownership is a unidimensional psychological construct. The participants of this research are employees of PT ABC which is a clothing retail company (n=66). Research method used is non-experimental and data is processed using linear regression analysis method. The result of the research shows that perceived organizational support and psychological capital have 34% effect on psychological ownership with F=16.246, p<0.05. On This research shows that psychological capital has more impact than perceived organizational support. From perceived organizational support variable, the dimension that has the most significant role to psychological ownership is organizational reward and from psychological capital variable, the dimension that has the most significant role to psychological ownership is resilience. Among these two free variables, psychological capital has the most significant role on psychological ownership.